Analisis Strategi Guru dalam Menanamkan Nilai Pendidikan Karakter pada Anak Sekolah Dasar - Yeni Nuraeni; Amanda Putri Humaeroh; Chiqa Arnabila Zahraan; Kumala Dewi; Rahma Izzatul Janah; Risma Odis Adellia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze teachers' strategies in instilling character education values in elementary school students based on various studies and references. Character education serves as a crucial foundation in shaping students' morals and attitudes, particularly at the elementary education level. Various studies reveal that the strategies implemented include role modeling, integrating character values into the learning process, case discussion methods, and reinforcement through constructive rewards or disciplinary actions. Furthermore, collaboration between teachers, parents, and the school environment significantly supports the success of character education implementation. This study provides insights that the success of character education requires a holistic approach involving all stakeholders to create a conducive learning ecosystem for students' character development.